ONLINE ROLE PLAY IN MANDARIN AS A FOREIGN LANGUAGE LEARNING BY USING GLOBAL CLASSROOM METHOD - Wee Ling, Kuan; Mei Feng, Kang (UMK Press Universiti Malaysia Kelantan Office of Library and Knowledge Management 16300 Bachok, Kelantan, 2021)
The paper reports a study on online role play in Mandarin as a Foreign Language(MFL) learning by using global classroom method. “Zoom” is the chosen videoconferencing tool for role play activity between Universiti Malaysia Sarawak (UNIMAS) and Universiti Malaysia Pahang (UMP). The participants of the study included 37 students who were enrolled in elementary MFL course from UNIMAS and UMP. The data were collected through an online questionnaire and students’ testimonial videos. The results indicated that even though there were some technological issues occurred, in overall, participants were satisfied with the activity. They were able to construct new knowledge and enhance their language skills.